2020
DOI: 10.1021/acssuschemeng.0c04532
|View full text |Cite
|
Sign up to set email alerts
|

Solution Growth of BiSI Nanorod Arrays on a Tungsten Substrate for Solar Cell Application

Abstract: One-dimensional nanostructure arrays hold great promise for orthogonalizing light absorption and carrier collection, and thus have been attractive building blocks for next-generation solar cells. Therefore, it is highly desired to build one-dimensional nanostructure arrays of novel photovoltaic materials. In this work, for the first time, the ternary BiSI nanorod arrays have been successfully fabricated on a tungsten substrate for application in solar cells. These nanorods have an oriented growth along the [00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 83 publications
1
35
0
Order By: Relevance
“…Therefore, developing methods to control and optimize the properties of chalcohalides suitable for solar cells is imperative. Sb/Bi chalcohalides used for solar cells are prepared by many techniques including spray pyrolysis [ 40 ], spin coating [ 24 , 45 , 46 , 47 , 51 ], solvothermal synthesis [ 49 , 53 ], and mixed techniques [ 23 , 38 , 48 , 65 ]. In this section, the fabrication methods reported to date are categorized and described, with the solar cells fabricated presented by the method in Table 4 .…”
Section: Sb/bi Chalcohalide Solar Cells Fabricationmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, developing methods to control and optimize the properties of chalcohalides suitable for solar cells is imperative. Sb/Bi chalcohalides used for solar cells are prepared by many techniques including spray pyrolysis [ 40 ], spin coating [ 24 , 45 , 46 , 47 , 51 ], solvothermal synthesis [ 49 , 53 ], and mixed techniques [ 23 , 38 , 48 , 65 ]. In this section, the fabrication methods reported to date are categorized and described, with the solar cells fabricated presented by the method in Table 4 .…”
Section: Sb/bi Chalcohalide Solar Cells Fabricationmentioning
confidence: 99%
“…Using this method, nanorod-based BiSI films with an E g value of 1.61 eV were obtained ( Figure 5 f,g). Recently, Xiong et al also reported the fabrication of BiSI nanorods arrays based on a two-step method [ 49 ]. However, their method involved the solvothermal synthesis instead of spin coating in each step, as illustrated in Figure 6 a.…”
Section: Sb/bi Chalcohalide Solar Cells Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some nanorod array films have been fabricated as light absorbers for new‐generation highly efficient solar cells. The light absorbers of nanorod array oriented parallelly to the carrier transporting direction can efficiently suppress optical reflection and improve light scattering and trapping [28] . Such radical junction device structure guarantees sufficient light absorption, charge generation, and carrier separation and transportation [29,30] .…”
Section: Introductionmentioning
confidence: 99%